2018
DOI: 10.1051/matecconf/201819201005
|View full text |Cite
|
Sign up to set email alerts
|

A study on the run length properties of the side sensitive group runs double sampling (SSGRDS) control chart

Abstract: The side sensitive group runs double sampling (SSGRDS) chart incorporates the control charting concepts of the side sensitive group runs (SSGR) and double sampling (DS) charts. The SSGRDS chart which combines the efficiency of its basic charts is an effective approach to increase the speed of mean shift detection. The performance of the SSGRDS chart, based on the average number of observations to signal (ANOS), median number of observations to signal (MNOS) and percentiles of the number of observations to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The zero-and steady-state OOC performance of these schemes were computed using the ANOS. Chong et al (2018) studied the run-length in more details by evaluating additional run-length properties for the work in Khoo et al (2015), i.e., the median and percentile number of observations to signal (these are denoted by MNOS and PNOS, respectively).…”
Section: Group-runs Schemementioning
confidence: 99%
“…The zero-and steady-state OOC performance of these schemes were computed using the ANOS. Chong et al (2018) studied the run-length in more details by evaluating additional run-length properties for the work in Khoo et al (2015), i.e., the median and percentile number of observations to signal (these are denoted by MNOS and PNOS, respectively).…”
Section: Group-runs Schemementioning
confidence: 99%
“…The sample of size n1 is used in stage 1, while in stage 2, the two samples are combined. Since then, many researchers have been developing the DS monitoring scheme (for some recent developments, see for example 3,7–12 ). Daudin 6 and Costa 13 reported that the DS trueX¯ monitoring scheme performs better than the Shewhart trueX¯ scheme; hence, these two articles and others suggest that for parametric schemes, the DS‐type schemes are superior to the basic Shewhart‐type schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of literature on DS schemes is based on the assumption of known IC process parameters (i.e. Case K), see for example: Costa (1994), Irianto and Shinozaki (1998), He, Grigoryan and Sigh (2002), Carot, Jabaloyes and Carot (2002), Khoo et al (2011), Lee, Torng and Liao (2012), Khoo et al (2013a), Costa and Machado (2015), Costa (2017), You (2017), Chong et al (2018), Khoo (2018, 2019), Malela-Majika and Rapoo (2019), Malela-Majika (2019), etc. Although there is a lots of research work based on Case K, in practice, the process parameters are generally unknown (i.e.…”
Section: Introductionmentioning
confidence: 99%